Microtubules as Major Regulators of Endothelial Function: Implication for Lung Injury - Karki, Pratap; Birukova, Anna A. (Frontiers in Physiology, 2021)
Endothelial dysfunction has been attributed as one of the major complications in COVID-19 patients, a global pandemic that has already caused over 4 million deaths worldwide The dysfunction of endothelial barrier is characterized by an increase in endothelial permeability and inflammatory responses, and has even broader implications in the pathogenesis of acute respiratory syndromes such as ARDS, sepsis and chronic illnesses represented by pulmonary arterial hypertension and interstitial lung disease. The structural integrity of endothelial barrier is maintained by cytoskeleton elements, cell-substrate focal adhesion and adhesive cell junctions. Agonist-mediated changes in endothelial permeability are directly associated with reorganization of actomyosin cytoskeleton leading to cell contraction and opening of intercellular gaps or enhancement of cortical actin cytoskeleton associated with strengthening of endothelial barrier. The role of actin cytoskeleton remodeling in endothelial barrier regulation has taken the central stage, but the impact of microtubules in this process remains less explored and under-appreciated. This review will summarize the current knowledge on the crosstalk between microtubules dynamics and actin cytoskeleton remodeling, describe the signaling mechanisms mediating this crosstalk, discuss epigenetic regulation of microtubules stability and its nexus with endothelial barrier maintenance, and overview a role of microtubules in targeted delivery of signaling molecules regulating endothelial permeability and inflammation.